Essential oils in diets for Nile tilapia juveniles: Productive performance and plasmatic biochemistry - Sosa, Bruno dos Santos [UNESP]; Moro, Evandro Bilha [UNESP]; Gomes, Ricácio Luan Marques [UNESP]; Cardoso, Matheus dos Santos [UNESP]; Cardoso, Leonardo Machado; Boscolo, Wilson Rogério; de Oliveira, José Dilson Silva; Signor, Altevir; Bittencourt, Fábio (Hindawi, 2020)
The objective of this study was to evaluate the inclusion of increasing levels of a commercial mix of essential oils (EOs) from cashew (Anacardium occidentale) and castor bean (Ricinus communis) as an additive in diets for Nile tilapia. Thus, 240 juveniles with an initial weight of 35.06 ± 1.02 g were distributed in a completely randomized design (four treatments and six replicates) in 24 cylindrical-tapered tanks; the fish were fed for 60 days, four times a day, diets containing increasing levels of EO (0.10, 0.15 and 0.20%) and a control diet (without the additive). After the experimental period, the animals were desensitized, and an aliquot of blood was collected for the biochemical analysis; they were subsequently euthanized for the evaluation of productive performance and fillet chemical composition. No significant differences (p >.05) were observed in the analyses of productive performance, fillet chemical composition, and triglycerides, VLDL, total proteins, urea and glucose. However, significant differences (p <.05) were observed in the analyses of total cholesterol, HDL and LDL. Inclusion above 0.15 of the additive showed an improvement in the levels of lipoprotein carriers, increasing HDL levels and decreasing LDL values, without interfering with the fish productive performance.
Keywords: cardanol; cardol; lipoproteins; natural antioxidant; ricinoleic acid; vegetable extract